2006
DOI: 10.1007/s00020-006-1453-1
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of the Kerzman-Stein Operator for the Ellipse

Abstract: Abstract. The skew-hermitian part of the Cauchy operator, defined with respect to arclength measure on the boundary, is known as the Kerzman-Stein operator. For an ellipse, the eigenvalues of this operator are shown to have multiplicity two. For an ellipse with small eccentricity, we compute the leading coefficient in the asymptotic expansion of the eigenvalues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Previously, the author gave descriptions of the Kerzman-Stein operator for certain model domains [3,4]. Here we evaluate the estimates of Theorems 1 and 2 for these known cases.…”
Section: Examplesmentioning
confidence: 98%
See 2 more Smart Citations
“…Previously, the author gave descriptions of the Kerzman-Stein operator for certain model domains [3,4]. Here we evaluate the estimates of Theorems 1 and 2 for these known cases.…”
Section: Examplesmentioning
confidence: 98%
“…In [3] it was shown that the spectrum of A for an ellipse with major and minor axes 2(1+r) and 2(1−r), respectively, consists of the values ±iβ n r 2n−1 + o(r 2n−1 ) valid asymptotically as r ↓ 0, for certain 0 < β n ≤ 1 and n = 1, 2, . .…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent work on the problem was concerned with giving a complete description of the spectrum for model domains [3], asymptotics of eigenvalues for ellipses with small eccentricity [5], and norm estimates that are invariant with respect to Möbius transformation [1,4]. For a disc or halfplane, there is complete cancellation of singularities and the Kerzman-Stein operator is trivial [13].…”
Section: Theoremmentioning
confidence: 99%
“…(Recall that the essential norm -see [13] -measures the distance to the set of compact operators; it often occurs in localized analysis.) See [5,9,10] for related results about C.…”
Section: Introductionmentioning
confidence: 99%